Ethnic Festivals and Revisiting Intentions: A Study of Cultural Tourism at Bali's Ogoh-Ogoh Festival - Reztrianti, Diajeng; Juanna, Andi; Haykal, Azzahra Putri; Wibowo, Setyo Ferry (Jambura Science of Management, 2025)
Purpose: This study aims to map the trends, major themes, theoretical frameworks, and key determinants of revisit intention within the literature on ethnic festivals, with a special focus on Bali’s cultural tourism context.Design/Methodology/Approach: A mixed-method approach was employed, integrating bibliometric analysis and systematic literature review (SLR) based on the SPAR-4-SLR protocol, encompassing the stages of assembling, arranging, and assessing. Literature searches and selections were conducted through the Scopus-indexed Emerald and ScienceDirect databases for the period May 2014–May 2025, yielding 22 core articles for analysis.Findings: The findings reveal that cultural authenticity, symbolic experience, and local community engagement are critical factors in creating memorable experiences and fostering tourists’ intention to revisit. The Ogoh-Ogoh and Nyepi festivals demonstrate distinctive symbolic and spiritual dimensions, although the international database on Ogoh-Ogoh remains scarce. These results underscore the need for collaborative, interdisciplinary research and broader theoretical integration to advance understanding of ethnic festivals’ roles in sustainable tourism. This study provides both conceptual and practical foundations for developing innovative, authentic, and sustainable strategies for cultural destination management at both local and global levels.